Novel Mutation of Exon 5 Prolactin Gene in IPB-D1 Chicken - Lailatul Rohmah; Sri Darwati; Niken Ulupi; Isyana Khaerunnisa; Cece Sumantri (Jurnal Ilmu Ternak dan Veteriner, 2020)
The prolactin gene (PRL) is a gene that controls the incubation and egg production in laying chickens. The nature of incubation will reduce egg production and disrupt the reproductive system in local chickens. The purpose of this study was to identify the polymorphism of prolactin genes in IPB-D1 chickens using the direct sequencing method. The polymorphism of the exon 5 prolactin gene was carried out on 46 samples of IPB-D1 chicken DNA which was a collection of the Division of Animal Genetics and Breeding, Faculty of Animal Science IPB. DNA sequences as a reference for designing exon 5 primers were obtained from the National Center for Biotechnology Information (NCBI) with the GenBank access code: AF288765.2. DNA extraction was carried out using the phenol-chloroform technique. DNA amplification resulted in a PCR product with a size of 557 bp. In this study, the genotype frequency, allele frequency, heterozygosity value and Hardy-Weinberg equilibrium were calculated. The results of the study found 5 SNPs in exon 5, namely g.7823A>G, g.7835A>G, g.7886T>A, g.8052T>C, and g.8069T>C. All SNPs are polymorphic and in Hardy-Weinberg equilibrium except g.8052T>C. The g.7823A>G, g.7835A>G, g.8052T>C SNPs are synonymous mutations that do not change amino acids, while the g.7886T>A and g.8069T>C SNPs are non-synonymous that change amino acids. Both g.7886T>A and g.8069T>C SNPs are potential as a marker assisted selection for the characteristics of egg production in IPB-D1 chickens.